Effect on crystalline structure of AISI M2 steel using copper electrode through material removal rate, electrode wear rate and surface finish. (February 2015) - Mandaloi, Gangaram; Singh, Subhash; Kumar, Pradeep; Pal, Kaushik
Graphical abstract: Based on the XRD results it has been found that the crystallographic structure of the AISI M2 steel has been totally changed after machining. In the un-machined surface it has been found that the matrix peaks correspond to α-Fe-ferrite with bcc structure at 44.83° and 82.49° are so sharp with high intensity. In XRD study it has been observed that the peak has been broadened and shifted with the formation of new nano crystalline phases (like WC, Fe2 O3 and Fe3 C) could be formed and also due to the homogeneous dispersion of the particles inside the matrix which give better material properties. Highlights: EDM has been used to study the effect on crystalline structure of the materials. OSP, AFM and XRD were used to study the crystallographic structure. Higher MRR of 0.015276 mg/min and minimum EWR of 0.014113 mg/min. Lowest SR of 9.25 ± 0.5 nm and 1.19 ± 0.9 μm was observed by AFM and OSP study. Abstract: A detailed investigation on the crystalline structure of AISI M2 steel by using copper alloy electrode in electric discharge machining (EDM) process has been done. Also, material removal rate (MRR), electrode wear rate (EWR) and surface roughness (SR) of the steel material on the basis of three variable input process parameters were analyzed followed by analysis of variance (ANOVA), regression analysis and different characterization techniques. In X-ray diffraction (XRD) study, it has been observed that the peak has been broadened and shifted with the formation of new nano crystalline phases. Lowest surface roughness of 1.19 ± 0.9 μm and 9.25 ± 0.5 nm was observed through optical surface profiler (OSP) and atomic force microscopy (AFM), respectively. Higher MRR of 0.015276 mg/min and minimum EWR of 0.014113 mg/min were observed for sample having the same input parameters as current 7 A, pulse on time 45 μs and spark gap of 5 μm.